Degradation of sulfamethoxazole in water by solar photo-Fenton. Chemical and toxicological evaluation - Trovo, Alam G. [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP]; Aguera, Ana; Fernandez-Alba, Amadeo R.; Sirtori, Carla; Malato, Sixto (Pergamon-Elsevier B.V. Ltd, 2009)
In this work, the photocatalytic degradation of the antibiotic sulfamethoxazole (SMX) by solar photo-Fenton at pilot plant scale was evaluated in distilled water (DW) and in seawater (SW). Degradation and mineralization of SMX were strongly hindered in SW compared to DW. The influence of H(2)O(2) and iron concentration on the efficiency of the photocatalytic process was evaluated. An increase in iron concentration from 2.6 to 10.4 mg L(-1) showed only a slight improvement in SMX degradation and mineralization. However, an increase in H(2)O(2) concentration up to 120 mg L(-1) during photo-Fenton in DW decreased SMX solution toxicity from 85% to 20%, according to results of Daphnia magna bioassays. The same behaviour was not observed after photo-Fenton treatment in SW. Despite 45% mineralization in SW, toxicity increased from 16% to 86% as shown by Vibrio fischeri bioassays, which suggests that the intermediates generated in SW are different from those in DW. A SMX degradation pathway during the photo-Fenton treatment in DW is proposed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Pharmaceuticals; Sulfamethoxazole; Advanced oxidation processes; Photo-Fenton; Degradation products; LC-TOF-MS; Toxicity